Educação profissional: análise dos efeitos de um curso técnico em secretariado na vida laboral dos egressos - Barroso, Fernanda de Queiroz (2007)
This essay aimed to analyze the influence of a high school level professional education course on the secretarial branch in the development of professional skills and also in the socioeconomic situation of their graduates. The professional education began with the aim of achieving a more targed qualification for the world of work in order to meet demands of the market that increasingly looks for people with ability to develop diverse professional skills. The role of secretarial professionals is prominently growing in global demand, in addition to be considered a profession which is undergoing major changes since its conception. The study was built on a descriptive as well as quantitative type of research. Documental and bibliographical studies were based on the work of distingued authors. Beyond that, the research was consolidated through the application of questionnaires completed by the students that accomplished the requirements of the Secretarial Technical Course offered by CETREDE-Development and Training Center, in Fortaleza. The answers were based on the influence of the course in the skills improvement and socioeconomic growth of their graduates, which results became significantly positive. The study provided a series of reflections that may help to encourage the implementation of new researches, emphasizing the importance of professional education as well as the importance of the secretarial professional worker.